Effect Of Infused White Dragon Fruit (Hylocereus undatus) Pell On Hemoglobin Level, Eritrosit Count, And Hematocrit Levels In Anemia White Rats: Pengaruh Infusa Kulit Buah Naga Putih (Hylocereus undatus) Terhadap Kadar Hemoglobin, Jumlah Eritrosit, dan Kadar Hematokrit Tikus Putih Anemia - Ardiansyah, Syahrul; Sielvi , Hanna; Handayani , Lailatul; Wulandari, Fitria Eka (Medicra (Journal of Medical Laboratory Science/Technology), 2022)
Anemia is a medical condition when the concentration of hemoglobin, erythrocytes, or hematocrit is less than average. The peels of white dragon fruit contains iron, vitamin C and flavonoids, which play an essential role as hemoglobin production. These flavonoids can increase erythropoiesis (erythrocyte formation process) and have immunostimulant effects. This research aimed to analyze the effect of giving peel undatus level infusion toward the number of hemoglobin, erythrocytes and hematocrit levels in anemia sufferer. Twenty-five male wistar rats given per oral injected with Natrium Nitrit before treatment. Wistar rats then grouped into five treatment groups, they are: the control group (without treatment), infusion of peels white dragon fruit with a concentration of 25%, 50%, 75%, and 100%. The results showed that there was a significant increase on the number of hemoglobin, erythrocytes and hematocrit levels of the rat after it was given with infusion of white dragon fruit peel. The conclution of this research is infusion of white dragon fruit peel increase the number of hemoglobin, erythrocytes and hematocrit levels.